Ion-pumping microbial rhodopsins - Kandori, Hideki (Frontiers in Molecular Biosciences, 2015)
Rhodopsins are light-sensing proteins used in optogenetics. The word “rhodopsin” originates from the Greek words “rhodo” and “opsis”, indicating rose and sight, respectively. Although the classical meaning of rhodopsin is the red-colored pigment in our eyes, the modern meaning of rhodopsin encompasses photoactive proteins containing a retinal chromophore in animals and microbes. Animal and microbial rhodopsins possess 11-cis and all-trans retinal, respectively, to capture light in seven transmembrane α-helices, and photoisomerizations into all-trans and 13-cis forms, respectively, initiate each function. Ion-transporting proteins can be found in microbial rhodopsins, such as light-gated channels and light-driven pumps, which are the main tools in optogenetics. Light-driven pumps, such as archaeal H+ pump bacteriorhodopsin (BR) and Cl- pump halorhodopsin (HR), were discovered in the 1970s, and their mechanism has been extensively studied. On the other hand, different kinds of H+ and Cl- pumps have been found in marine bacteria, such as proteorhodopsin (PR) and Fulvimarina pelagi rhodopsin (FR), respectively. In addition, a light-driven Na+ pump was found, Krokinobacter eikastus rhodopsin 2 (KR2). These light-driven ion-pumping microbial rhodopsins are classified as DTD, TSA, DTE, NTQ and NDQ rhodopsins for BR, HR, PR, FR and KR2, respectively. Recent understanding of ion-pumping microbial rhodopsins is reviewed in this paper.